Validity of the EQ‐5D in patients with pemphigus vulgaris and pemphigus foliaceus. (1st April 2019) - Tamási, B.; Brodszky, V.; Péntek, M.; Gulácsi, L.; Hajdu, K.; Sárdy, M.; Szegedi, A.; Bata‐Csörgő, Z.; Kinyó, Á.; Rencz, F.
Summary: Background: No studies to date have employed the EuroQoL EQ‐5D questionnaire to assess health‐related quality of life (HRQoL) in patients with pemphigus. Objectives: To evaluate the HRQoL of patients with pemphigus by the EQ‐5D and to analyse the convergent and known‐groups validity of the EQ‐5D in this patient population. Methods: Between 2014 and 2017, a multicentre cross‐sectional study was carried out. Outcome measures included the five‐level EQ‐5D (EQ‐5D‐5L), Dermatology Life Quality Index (DLQI), Autoimmune Bullous Skin Disorder Intensity Score (ABSIS) and an average pain intensity visual analogue scale (VAS) for the past 3 months. Results: In total, 109 consecutive patients with pemphigus participated in the study (mean age 57 years; 64% women). Among the EQ‐5D dimensions, the most problems were reported regarding pain/discomfort (50%), mobility (43%) and anxiety/depression (43%). No significant difference was found in mean EQ‐5D index scores between patients with pemphigus vulgaris and those with pemphigus foliaceus (0·81 vs. 0·86, P = 0·14). The mean EQ‐5D index scores of patients with limited, moderate, significant and extreme pemphigus were 0·88, 0·82, 0·72 and 0·67, respectively ( P = 0·001). The number of comorbidities was associated with greater impairment in EQ‐5D index scores ( P < 0·001). DLQI ( r s = −0·62, P < 0·001) and the average pain intensity VAS ( r s = −0·59, P < 0·001) more strongly correlated with the EQ‐5D index scores than did ABSIS ( r s = −0·40, P < 0·001). Conclusions: This is the first study employing the EQ‐5D questionnaire in pemphigus. The EQ‐5D is a valid measure of HRQoL in patients with pemphigus that can be useful both in clinical practice and in economic evaluations to assess the health gains associated with new effective treatments.